Biodegradability of bioplastic blown film in a marine environment - Phosri, Santi; Kunjiek, Tikumporn; Mukkhakang, Chaninta; Suebthep, Sililuck; Sinsup, Wannisa; Phornsirigarn, Sasithorn; Charoeythornkhajhornchai, Pollawat (Frontiers in Marine Science, 2022)
The waste of single-use plastics has been an important issue all over the world, especially for marine environment because it does not degrade in the environment. This work aim to study the biodegradability of bioplastics blown film that might be solved this problem. Polybutylene succinate (PBS) and polylactic acid (PLA) blown film were chosen to examine the biodegradability of these bioplastics that were submerged in the sand under the sea water and floated on the sea water surface of our experimental setup. Bioplastics was observed compared to polyethylene (PE) that was the petroleum based plastics. PBS blown film exhibited faster degradation rate than PLA blown film while PE blown film did not degrade under marine environment. The degradability of bioplastics blown film was confirmed by physical observation, the change of chemical functional group measuring by Fourier-transform infrared spectroscopy (FTIR) and the test of biochemical oxygen demand (BOD) of the sea water after bioplastics degradation due to the ingestion of the bacteria in the sea water.